2015
DOI: 10.1007/s13277-015-4184-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfibrinogenemia predicts poor prognosis in patients with advanced biliary tract cancer

Abstract: Hyperfibrinogenemia reportedly predicts poor prognosis in several cancers but has not been reviewed for biliary tract cancer (BTC). The aim of the present study was to evaluate associations between baseline plasma fibrinogen concentrations, clinicopathological characteristics, and survival parameters in patients with BTC. Data for 127 patients with BTC diagnosed at the Zhongshan Affiliated Hospital of Dalian University (Liaoning, China) from January 2011 to December 2014 were retrospectively evaluated. Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Our results are in accordance with previous studies of other types of tumors. [9,24] The mechanism underlying this association may be the binding of fibrinogen to members of the transforming growth factor-B, vascular endothelial growth factor, platelet-derived growth factor, and fibroblast growth factor gene families, thereby leading to the inhibition of apoptosis, angiogenesis, and metastasis and promotion of tumor cell proliferation. [8,25] Platelet-fibrin microthrombi appear to act as a physical barrier, preventing contact between natural killer cells and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in accordance with previous studies of other types of tumors. [9,24] The mechanism underlying this association may be the binding of fibrinogen to members of the transforming growth factor-B, vascular endothelial growth factor, platelet-derived growth factor, and fibroblast growth factor gene families, thereby leading to the inhibition of apoptosis, angiogenesis, and metastasis and promotion of tumor cell proliferation. [8,25] Platelet-fibrin microthrombi appear to act as a physical barrier, preventing contact between natural killer cells and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided strong evidence that plasma fibrinogen is associated with tumor progression and poor prognosis in lung cancer, [4] breast cancer, [5] gastric cancer, [6] ovarian cancer, [7] oral and oropharyngeal cancer, [8] biliary tract cancer, [9] and penile cancer [10] patients. Fibrinogen is a 340-kDa glycoprotein that is synthesized in the liver and converted into fibrin by active thrombin.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100] Hyperfibrinogenemia is increasingly recognized as an important risk factor influencing cancer development and outcome, associated with poor prognosis in various cancers (e.g., ovarian, biliary, esophageal, and pancreatic). 26,[101][102][103][104][105][106] Globally, an elevated content of FBG in plasma before treatment significantly correlates with decreased survival in patients with solid tumors. 107 Recently, in rectal cancer tissues, Repetto et al 108 identified FBG ␤ chain as a marker for identification of poor responders before therapy.…”
mentioning
confidence: 99%
“…So the fibrinogen may take part in the adhesive interaction among tumor cells or endothelial cells, and lead to hematogenous metastasis [30, 31]. Elevated levels of plasma fibrinogen are reported to be an useful prognostic predictor for several types of human cancers [1519]. So we aim to clarify the prognostic ability of fibrinogen in HCC patients after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects inflammatory response of the host to cancer as well as the systemic inflammation mediated by tumor [14]. Previous studies have shown that preoperative hyperfibrinogenemia and NLR were associated with the progression and poor prognosis of several cancers, such as colorectal [15], gastric [16], pancreatic [17], and lung cancer [18], biliary tract cancer [19], HCC [20]. However, the relationship between plasma Fib concentration and prognosis of HCC patients with after liver transplantation is not very clear, especially the prognostic value of Fib in combination with NLR has not been determined.…”
Section: Introductionmentioning
confidence: 99%